PERANAN PENYIDIK POLRI DALAM TINDAK PIDANA YANG TERKAIT DENGAN PENEMPATAN TENAGA KERJA INDONESIA DI LUAR NEGERI (Studi Pada Kepolisian Daerah Sumatera Utara) - ROBERT HARYANTO WATRATAN (USU LAW JOURNAL, 2013)
Human trafficking is a crime. TKI (Indonesian workers), especially children, in foreign countries are vulnerable to be the object of human trafficking. The police has strategic role in preventing and eradicating it and illegal TKI placement. The regulation on criminal act in the placement of TKI in foreign countries only states that illegal individuals are prohibited to send TKI to foreign countries or illegal TKI is prohibited. The role of Polda Sumut investigators is to optimize the relationship among nations. The obstacles faced by Polda Sumut can be judicial and non-judicial. Some efforts are to increase preemptive, preventive, and repressive actions. It is recommended that Law No. 1/2006 on Mutual Legal Aid in Criminal Act should be optimized, the national interest principle of the Aid Requesting Countries should be prioritized to accelerate the process of law enforcement in the Aid Requesting Countries, and prevention should be more prioritized than eradication. Kata Kunci:   Keywords: Role of Police Investigators, Placement of TKI in Foreign Countries, Human Trafficking Criminal Act